Analysis of ethoxyquin residues in animal feed using QuEChERS and gas chromatography tandem mass spectrometry and its results from Catalonian production 2018–2019. Issue 32 (6th August 2020) - Sanchez Costa, Laia; Pujol Boira, Judit; Aragó Iglesias, Miriam; Rodríguez Martínez, Pilar; Medina Sala, Mireia
Abstract : Regulation (EU) 2017/962 suspended ethoxyquin authorisation as a feed additive for all animal species. This method allows the fast and efficient determination of ethoxyquin in complex matrices and becomes a crucial tool for agri-food laboratories. Abstract : Ethoxyquin (EQ) is a quinolone commonly used as an antioxidant additive and a fungicide. However, Regulation (EU) 2017/962 suspended its authorisation as a feed additive for all animal species and categories. The aim of this study is thus to ensure compliance with this regulation by developing a method of analysing EQ in animal feed. For analysis, EQ was extracted from animal feed by using a modified QuEChERS protocol that used an ascorbic acid buffer to minimise its degradation. The extracts were analysed by gas chromatography coupled to triple quadrupole mass spectrometry (GC-QQQ), obtaining two chromatographic peaks corresponding to EQ and its transformation products. A study of these peaks was subsequently carried out using different standards, evincing that EQ had indeed been converted into several different transformation products. Quantification required the sum of the areas of the different peaks. The method was validated according to European Commission guidelines, namely SANTE/12682/2019. The obtainment of pesticide-free samples for carrying out the validation process was a critical achievement, as EQ residues were detected in 90% of the analysed samples. This was made possible by manufacturing 20 different feed samples from a mixture of several cereals used in animal feed in the laboratory. Method validation yielded excellent results in terms of accuracy (recoveries 70–120%), precision (RSD < 20%) and linearity ( r 2 ≥ 0.99) at the studied levels, as well as excellent sensitivity and selectivity (retention time ±0.1 min; ratio < 30%) to the LoQ. Over the course of 2018 and 2019, 70 samples of various feed matrices from agricultural production in Catalonia were analysed, garnering positive results 43% of the time.